1994
DOI: 10.1093/jac/33.3.537
|View full text |Cite
|
Sign up to set email alerts
|

The activity of 2-substituted quinoline alkaloids in BALB/c mice infected with Leishmania donovani

Abstract: Potent antileishmanial activity has recently been described in vivo when certain 2-substituted quinoline alkaloids are administered to mice with cutaneous leishmaniasis. We now report the antileishmanial activity of four 2-substituted quinoline alkaloids, namely chimanine D or 2-(1',2'-trans-epoxypropyl) quinoline (I), 2-n-propylquinoline (II), 2-styrylquinoline (III) and 2-(2'-hydroxypropyl) quinoline (IV), for experimental treatment of visceral leishmaniasis in infected BALB/c mice. Subcutaneous treatment wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 10 publications
0
32
0
1
Order By: Relevance
“…Dentre eles, podem ser citados os terpenóides (Yang;Liew, 1992;Camacho et al, 2000), aminoglicosteróides e aminosteróides (Kam et al, 1997), naftoquinonas (Fournet et al, 1992a;Kayser et al, 2000), chalconas (Chen et al, 1993), glicosídios iridóides (Mittal et al, 1998); fl avonóides (Araújo et al, 1998), neolignanas (Barata et al, 2000) e os alcalóides (Mahiou et al, 1994;Fournet et al, 1994;Queiroz et al, 1996;Akendengue et al, 1999).…”
Section: Discussionunclassified
“…Dentre eles, podem ser citados os terpenóides (Yang;Liew, 1992;Camacho et al, 2000), aminoglicosteróides e aminosteróides (Kam et al, 1997), naftoquinonas (Fournet et al, 1992a;Kayser et al, 2000), chalconas (Chen et al, 1993), glicosídios iridóides (Mittal et al, 1998); fl avonóides (Araújo et al, 1998), neolignanas (Barata et al, 2000) e os alcalóides (Mahiou et al, 1994;Fournet et al, 1994;Queiroz et al, 1996;Akendengue et al, 1999).…”
Section: Discussionunclassified
“…In addition to the preceding agents (tested in targeted and free form), review of the 1990-2000 literature indicates more than a dozen other agents with in vivo activity in experimentally infected animals (2,3,38,47,52,63,65,66,104,149,191). The selection of study drugs has been eclectic and largely empiric, and their broad array defies useful classification.…”
Section: New Antileishmanial Agents or Application Of Existing Drugsmentioning
confidence: 99%
“…Two quinolines (quinolines 3 and 7) were specifically active against cutaneous leishmaniasis, and two quinolines (quinolines 4 and 5) were only active against visceral leishmaniasis infection. We observed that 2-alkenylquinoline 3 (containing a pent-2-en-1-yl chain) had antileishmanial properties similar to those of prop2en-1-yl quinoline previously described and isolated from the Bolivian plant Galipea longiflora (10,11). With these new analogs, we can now confirm (i) their oral efficacy and (ii) the recent in vitro results obtained against the amastigote forms of L. amazonensis, L. infantum, and L. donovani (9).…”
Section: Vol 49 2005 Efficacy Of 2-substituted Quinolines In Leishmmentioning
confidence: 55%
“…Following this approach, we have previously reported the efficacy of 2-substituted quinolines in the experimental treatment of cutaneous and visceral leishmaniasis by oral and parenteral routes (10,11).…”
mentioning
confidence: 99%